Pencegahan dan Peningkatan Kualitas Permukiman Kumuh di Kabupaten Bogor: - - Pujiyono, Bambang; Arfian; Rudi Subiyakto (DRPM Universitas Budi Luhur, 2021)
This study aims to describe the linkages of various policies in improving the quality of slum settlements in Bogor Regency. The focus of this research is on the scope of policy content and policy implementation. The study used a qualitative approach, sourced from secondary data which was explored through discussions with activists in the slum area of BPM KOTA. Data analysis was carried out descriptively by giving analytical power to data or phenomena that were still within the scope of the research focus. The results of the study illustrate that coordination and integration between policies at various levels of the bureaucracy has not yet touched the technical level in solving the problem of improving the quality of slum settlements in urban areas